PENDAMPINGAN INTERNALISASI NILAI-NILAI MODERASI BERAGAMA DALAM PRAKTIK TRANSAKSI DI KOPERASI PONDOK PESANTREN DAERAH KADUR PAMEKASAN - Jailani, Jailani - (BAJHRAH: JURNAL PENGABDIAN KEPADA MASYARAKAT, 2025)
Abstract Community Service Program (PKM). This is intended to accompany the process of internalizing the value of religious moderation in the practice of economic transactions in cooperatives with Al Wardah. An Islamic boarding school located in the Kadur District area. Pamekasan Regency. Along the way, the phenomenon of economic development aims not only for profit but also for Islamic values, promoting the importance of integrating religious moderation and the principles of trade in accordance with the unity of justice, tolerance and inclusion. Implementation methods include participatory observation, training courses, and structured discussions between management and cooperative management. The results of the study showed an increase in understanding of cooperative stakeholders regarding the importance of the principle of religious moderation. This is reflected in the practice of transparent trade, justice, and maintenance of the principles of Togetherness. In addition, there is a collective awareness that develops that cooperatives are not only economic institutions, but also character formation in cars and propaganda. PKM recommends strengthening participating entrepreneurs based on the values ​​of sustainability and religious moderation of their development programs. "The program (PKM) that supports the internalization of moderate religious values ​​in trade practices in the local Islamic Boarding School environment in Kadur District aims to be an activity in the Islamic Boarding School cooperative. Activities such as focused group discussions, training, and direct training are carried out to provide a deeper understanding of the importance of religious moderation in transactions. Through this program, the Islamic Boarding School cooperative in the distribution of Members is not only a way to strengthen the economy, but also an example of the use of moderate religious values ​​in the Islamic boarding school area. Based on the explanation above, it is concluded that the unprofitable service in the Cooperative alone, Kadur Pamekasan Regency, is implemented correctly in accordance with the expected goals of the schedule. Keywords: religious moderation, cooperative transactions, Islamic boarding schools, strengthening values, PKM